PENGARUH STRUKTUR KEWENANGAN, KARAKTERISTIK SISTEM INFORMASI KEUANGAN DAERAH DAN PERILAKU MANAJER TERHADAP KESADARAN AKAN BIAYA (STUDI EMPIRIS PADA PEMERINTAHAN DAERAH KABUPATEN SIAK) - Kusuma, Wira Ade; Kirmizi, Kirmizi; Agusti, Restu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
This research aims to analyze and determine the influenceof the authority structure, regional characteristics of financialinformation systems, and the behavior of managers towards costconciousness. This research was conducted throughout theDepartment/ Agency/ Office of Siak . The sample in this study is allSKPD Head (Department/ Agency/ Office of Siak) as budget officerswhich consists of 15 agency heads, 8 agency heads, 18 head of officeand secretariat, 1 head of hospitals and 1 Inspectorate. Furthermore,the financial section for each department, agency, office andsectretariat 1, so that the entire sample was 65 people, taken bypurposive sampling method . While the analysis of data usingmultiple regression models. The results of this study stated thatformal authority, financial information systems and behaviours ofmanager in Siak Regency, Riau province has a significant effect onincreased of the cost conciousness. While informal authority in SiakRegency, Riau province has no significant effect on the increasedofthe cost conciousness. The coefficient of determination by Adj R2 =0.923 . This means that the cost conciousness in Siak Regency of RiauProvince is affected by the independent variable (formal authority,informal authority, financial information systems and managerbehavior) are of 93.2 % . While approximately 7.8 % is influenced byother variables.